EVALUASI PENERAPAN PSAK-69 AGRIKULTUR TERHADAP ASET BIOLOGIS (Studi pada Perusahaan Perkebunan Pertanian yang Terdaftar di Bursa Efek Indonesia tahun 2012-2017) - Adelia Yohana Meilansari; Maslichah Maslichah; Muhammad Cholid Mawardi (Universitas Islam Malang, 2019)
AbstractBeginning in 2016 the DSAK (Accounting Standards Board) issued an exposure draft PSAK-69 agriculture in which this PSAK is a full deduction of IAS-41 agriculture. IAS-41 agriculture is an accounting standard devoted to agricultural entities in applying accounting for their biological assets. The year of 2018 is the year in which Indonesia requires all agricultural entities to adopt PSAK-69 agriculture. This research was conducted at Plantation companies listed on the Indonesian stock exchange in 2012-2017. The purpose of this study is to provide empirical evidence regarding the accounting treatment of biological assets according to PSAK-69 agriculture compared with those in plantation companies listed on the Indonesian stock exchange in 2012-2017. The result of this research is actually not much different between PSAK-69 agriculture and accounting treatment at Plantation companies listed on the Indonesian stock exchange, it’s just the measurement of the biological assets of the company uses the acquisition price while in PSAK 69 it is recommended to recognize it at fair value..Keywords : Biological Assets, PSAK-69 Agriculture and Fair Value.